New Media and Traditional Mass Media in Communiative Field - Serhii Honcharuk; Arthur Shurypa (Вісник Київського національного університету культури і мистецтв. Серія: Аудіовізуальне мистецтво і виробництво, 2019)
The purpose of the work is to consider new media and traditional mass media in the communicative field. Methodology of the study consists in the methods of theoretical sources analyzing, a generalization, a system analysis method, data grouping, and theoretical cognition. Scientific novelty of the work lies in the fact that the specifics of the relationship between television and the Internet (new media and traditional media in the information field) have been clarified, and the main trends in the modern and traditional media development have been illuminated. Conclusions. Even despite a significant amount of research on this topic, this issue is still not sufficiently studied. Considering the fact that modern technologies haven’t been explored yet, new forms of media (new television and media) are emerging that require detailed consideration.